Ekonomi Islam: Jumlah Tenaga Kerja, Disparitas PAD Dan Jumlah Industri Besar Terhadap Aglomerasi Industri - Samudra, M Andi; Putri, Rosydalina; Setyanto, Alief Rakhman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research is motivated by the imbalance in industrial concentration in the Southern Sumatra (Sumbagsel) region which has the potential to hinder the realization of equitable economic development. The main problem studied is the influence of the number of workers, disparity in Regional Original Income (PAD), and the number of large industries on industrial agglomeration from an Islamic economic perspective. This study aims to analyze the relationship between these variables and formulate the implications of equitable and sustainable industrial development policies. The study uses an associative quantitative approach with panel data regression analysis techniques in five provinces in the Sumbagsel region during the period 2015–2024. Model selection was carried out through the Chow, Hausman, and Lagrange Multiplier tests, with the results showing that the Random Effect Model (REM) is the most appropriate model. The results show that simultaneously all independent variables have a significant effect on industrial agglomeration, with an F-statistic value of 21.54681 and a probability of 0.0000 (<0.05). However, partially, it was found that the number of workers had a negative and significant effect on industrial agglomeration (coefficient -0.011283; p < 0.05), indicating a mismatch in skills and a mismatch in the quality of the workforce with industrial needs. Meanwhile, the disparity in local revenue (coefficient 0.010390; p > 0.05) and the number of large industries (coefficient 0.000618; p > 0.05) did not show a significant effect. This finding confirms that the quality of the workforce is a more crucial determinant than quantity in encouraging the formation of efficient, inclusive, and sustainable industrial agglomeration.